COMPARISON OF THE INDONESIAN LAW SYSTEM AND THE DUTCH LEGAL SYSTEM IN HANDLING THE CRIME OF CORRUPTION - Moh Nafri; Maisa Maisa (Fakultas Hukum Universitas Muhammadiyah Palu, 2022)
Justice Collaborator” is a new thing in the legal provisions in Indonesia. A witness who knows firsthand whether he is directly involved in it or not and dares to report the incident is called a witness “whistleblower” and “justice collaborator”. Be more specific on “justice collaborator” is the witness of the perpetrator who cooperated based on the Circular Letter of the Supreme Court of the Republic of Indonesia number 4 of 2011 concerning the Treatment of Whistleblowers of Crime (Whistleblower) and Collaborating Perpetrators (Justice Collaborator) in certain criminal cases. The research method uses normative legal research that uses primary and secondary legal materials. The processing of legal materials is basically a series of activities to systematize or classify written legal materials to facilitate the analysis of primary legal materials. The results of the study found, there are no laws and regulations that specifically regulate justice collaborators and the disparity between law enforcers has a negative impact on not being given respect and protection for justice collaborators in Indonesia. That is, the role of justice collaborators to uncover crimes more broadly, deeper, faster is not taken into account at all by law enforcers, especially the regulations that govern them. Keywords: Law System. Legal System. Corruption